The Effect Of Using The Listening Triangle Strategy In Acquiring Scientific Concepts Among First-Grade Intermediate Students In Science. (Journal of the College of Basic Education, 2024)
The research aims to identify the effect of using the listening triangle strategy in acquiring scientific concepts among first-grade intermediate students in science. The following null hypothesis was formulated:- There are no statistically significant differences at the level of significance 0.05 between the average scores of the experimental group students, who are taught according to the strategy (listening triangle), and the average scores of the control group students, who are taught according to the usual method in the test to acquire scientific concepts.The researcher used the experimental design with the post-test, and the research sample was first-grade students intermediate in Al-Dhariyat School of Education Baghdad Governorate Karkh II, numbering (60) students by (29) students in the experimental group and (31) students in the control group has been rewarded the two groups in the previous achievement and previous information and intelligence test and was statistically insignificant, and the researcher prepared a test acquisition of scientific concepts consists From (60) paragraph of the type of multiple choice with four alternatives and a representative of the three components of the concept (definition, discrimination and application) and confirm its sincerity, and the stability coefficient was calculated and the percentage of agreement (0.82) and the results were in favor of the experimental group, which was studied according to the strategy (listening triangle) in the test of acquiring scientific concepts, the researcher has come out with some recommendations and proposals